2013
DOI: 10.1371/journal.pone.0083042
|View full text |Cite
|
Sign up to set email alerts
|

Association between Traffic-Related Air Pollution, Subclinical Inflammation and Impaired Glucose Metabolism: Results from the SALIA Study

Abstract: BackgroundEnvironmental and lifestyle factors regulate the expression and release of immune mediators. It has been hypothesised that ambient air pollution may be such an external factor and that the association between air pollution and impaired glucose metabolism may be attributable to inflammatory processes. Therefore, we assessed the associations between air pollution, circulating immune mediators and impaired glucose metabolism. MethodsWe analysed concentrations of 14 pro- and anti-inflammatory immune medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…In a study of 8,018 residents (prevalence of T2DM=8%) from Westfriesland, Netherlands, NO 2 was not associated with the prevalence of T2DM [17]. A study conducted in the SALIA cohort, Germany (N=363, 100% women, prevalence of IGM=48%) found significant positive associations of IGM with NO 2 (OR=1.47 (95% CI, 1.05, 2.05) per IQR increase) and NO x (OR=1.41 (95% CI, 1.01, 1.97)) [28]. Finally, in an ecological study of the association between county-level PM 2.5 concentrations and diabetes prevalence in the US [25], a 10 μg/m 3 increase in PM 2.5 was associated with a 1.15% (95% CI, 1.02, 1.32%) increase in the diabetes prevalence in 2004 and a 0.92% (95% CI, 0.75, 1.13%) increase in 2005.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 8,018 residents (prevalence of T2DM=8%) from Westfriesland, Netherlands, NO 2 was not associated with the prevalence of T2DM [17]. A study conducted in the SALIA cohort, Germany (N=363, 100% women, prevalence of IGM=48%) found significant positive associations of IGM with NO 2 (OR=1.47 (95% CI, 1.05, 2.05) per IQR increase) and NO x (OR=1.41 (95% CI, 1.01, 1.97)) [28]. Finally, in an ecological study of the association between county-level PM 2.5 concentrations and diabetes prevalence in the US [25], a 10 μg/m 3 increase in PM 2.5 was associated with a 1.15% (95% CI, 1.02, 1.32%) increase in the diabetes prevalence in 2004 and a 0.92% (95% CI, 0.75, 1.13%) increase in 2005.…”
Section: Resultsmentioning
confidence: 99%
“…For the incidence and prevalence studies and observational diabetes mortality studies, either annual concentrations of particulate matters (mostly PM 2.5 or PM 10 and PM 10–2.5 (coarse particles)) or nitrogen oxides (NO x or NO 2 ) which were estimated using land-use regression [10, 11, 15, 17, 2628, 30] or satellite-based approach [13] were used as exposure metrics, whereas ecological studies of DM mortality or hospital/emergency admissions (except the study by Kloog et al [22]) used daily concentrations of criteria pollutants (PM 2.5 , PM 10 , NO 2 , CO, SO 2 , and O 3 ) based on central monitoring or the nearest monitors. Given the differences in study design and disease etiology between long-term air pollution effects on the development of T2DM vs. short-term air pollution effects on daily diabetes mortality or morbidity, we discussed causal relationships based on epidemiologic findings by these two study designs separately.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also found positive associations between ambient and traffic-related air pollutants and impaired glucose metabolism (3,4), with most studies assessing the impact of acute exposures. A study in Taiwan documented that elevated 5-day average O 3 was associated with increased fasting glucose (4).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few human studies have been performed and have suggested that short- and long-term exposure to air pollutants adversely affects key T2D-related pathways including glucose metabolism (3,4), insulin resistance (58), and dyslipidemia (4,9). While most previous studies have been conducted among Caucasians (3,7) and Asians (4,8), the effects in other populations with generally higher risk for T2D, such as Latinos (10) and African Americans (11), have not been adequately studied. Additionally, the informativeness of results from these studies is limited by the use of surrogate indices of insulin resistance, for example, HOMA of insulin resistance (HOMA-IR), which have well-documented limitations compared with detailed measures of insulin resistance such as intravenous glucose tolerance test and glucose clamps.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is another potential mechanism explaining the associations reported in this meta-analysis. There is high possibility for the activation of the inflammatory pathway and oxidative stress pathway by particulate matter (38,39,40). Previous studies also suggest that PM2.5 can recruit inflammatory cells via CC chemokine receptor 2-dependent mechanism, which is a known inflammatory mechanism in the pathogenesis underlying the association between air pollution and type 2 diabetes (35,41).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%